Laser‐induced metastable mixed phase of AuNi nanoparticles: a coherent X‐ray diffraction imaging study. (31st March 2020) - Kim, Yoonhee; Kim, Chan; Ahn, Kangwoo; Choi, Jungwon; Lee, Su Yong; Kang, Hyon Chol; Noh, Do Young
Abstract : Coherent diffraction imaging in the forward‐scattering geometry reveals AuNi nano alloy particles in a metastable mixed phase. The AuNi nanoparticles irradiated by nanosecond laser pulses exhibit the mixed phase overcoming the miscibility gap. Abstract : The laser annealing process for AuNi nanoparticles has been visualized using coherent X‐ray diffraction imaging (CXDI). AuNi bimetallic alloy nanoparticles, originally phase separated due to the miscibility gap, transform to metastable mixed alloy particles with rounded surface as they are irradiated by laser pulses. A three‐dimensional CXDI shows that the internal part of the AuNi particles is in the mixed phase with preferred compositions at ∼29 at% of Au and ∼90 at% of Au.